E-GOVERNMENT DALAM SDGS: PENERAPAN WEBSITE SEBAGAI UPAYA MENDUKUNG KEBERLANJUTAN PEMBANGUNANDI PROVINSI SUMATERA SELATAN - Kencana, Novia (Yayasan Panca Bakti Wiyata Pangandaran, 2025)
This study aims to analyze the implementation of the sdgs.sumselprov.go.id website as an effort to support the development of e-government in the sustainable development goals (SDGs) point of strong institutions in South Sumatra Province. The type of research used in this study is descriptive qualitative research with a literature review method. This study uses the theory and model of E-Government by Hiller's and ASPA's Five-Stage. This model is a theory created by Hiller to explain the implementation of E-Government in providing web-based public services through five stages or indicators. From the results of the analysis, it can be concluded that the implementation of e-government has reached the third stage, namely the Interactive Web presence stage (the presence of an interactive website). At this stage, it shows that the implementation of e-government in supporting strong institutional efforts is quite good but not yet optimal. Keywords: E-Government, SDGs, Strong Institutions, Sumatera Selatan.